Some key issues in information systems, databases and big data integration - Chittayasothorn, Suphamit (My University, 2019)
Databases and big data integration are keywords which attract attentions from both government and private sectors' administrators. In general, the term big data refers to data of large volume which come in different varieties and high velocity. Typical big data sources are from sensors of various kinds and social media. Transactional data from enterprise information systems with traditional structured databases are also major data sources for management decision support systems. This paper presents some key big data and database integration issues and suggests the level of integration required.
Keywords: Data Warehouse; Database Integration; Identifiers; Information Systems Integration; Ontology